Construcción de paz y conflicto armado: reflexiones desde el derecho y la publicidad - Rico Zapata, Jorge Andrés; Berrío-Meneses, Carlos; Montoya García, Daniela; Isaza Álvarez, Jimena; Carmona Toro, Paola Andrea; Molina Gómez, Richard Stivens; Tamayo Duque, Julián Andrés; Roldán-Villa, Ana María; Cardona-Zuleta, Elvigia; Arias Ramírez, María Fernanda (Universidad Católica Luis Amigó, 2026)
Peacebuilding and Armed Conflict: Reflections from Law and Advertising is an effort to integrate two fields which, despite having dissimilar objects of knowledge, converge in the study and understanding of essential issues within the Colombian context: armed conflict, peacebuilding, and transitional justice. Legal science, through normative developments, doctrine, and jurisprudence, has made important contributions to the characterization of the constitutive elements of armed conflict and to the strategies aimed at overcoming it and transitioning toward a peaceful society. Advertising, for its part, plays a predominant role through the construction of narratives that, on the one hand, make visible the agreements reached between the parties to the conflict including negotiated reparation measures and, on the other, influence public perception, as well as acceptance of or resistance to them.